THE RELEVANCE OF THROMBOLYTIC THERAPY IN ST ELEVATION MYOCARDIAL INFARCTION - N. V. Teplova; E. O. Taratukhin (Российский кардиологический журнал, 2014)
The article is about contemporary views on thrombolytic drugs usage. Although there is a great improvement in endovascular treatments, systemic thrombolysis is still one of the most important approaches to MI with ST elevation. The data of a few studies of thrombolytics with percutaneous intervention is provided, as with it or instead of it. Also the importance of thrombolytic drug pharmacokynetic profile is underlined.